Integrated Conversion of Desalination Waste Heat into Chemical Energy Using a Reversible Copper-Chlorine Thermochemical Cycle for Hydrogen Storage - Enas Eltnay (AlQalam Journal of Medical and Applied Sciences, 2026)
The growing global need for fresh water and clean energy has prompted huge concerns about combining the desalination processes with hydrogen production systems. In this study, the researcher has given an in-depth discussion of how the waste heat of desalination plants can be used to power a reversible copper-chlorine thermochemical cycle to generate and store hydrogen. The copper-chlorine cycle has a comparatively lower operating temperature, 300–550 °C, compared to other thermochemical cycles, so it is especially applicable in combination with desalination waste heat streams. The paper compares the thermodynamic performance, energy efficiency, and economic viability of such an integrated system. Not only does the proposed system reduce the energy intensity issues associated with desalination, but it also offers a solution to the sustainable production of hydrogen using thermal energy, which is otherwise wasted. Findings indicate that the combined system can produce hydrogen at efficiencies of 35–42% and, at the same time, save up to 18–25% of the specific energy used in desalination. The reverse of the thermochemical reaction allows hydrogen storage via chemical bond to be easily stored, which has some benefits over the commonly used compression and liquefaction. Economic studies show that the cost of hydrogen production is at par between 3.2–4.8 /kg, which is competitive when the desalination and hydrogen production are looked at as a two-fold purpose. This combination approach is an encouraging alternative to sustainable solutions of the water-energy nexus in areas with high desalination capacity.